Biosynthesis of polyketides by trans-AT polyketide synthases in Burkholderiales. (4th March 2019) - Chen, Hanna; Bian, Zhilong; Ravichandran, Vinothkannan; Li, Ruijuan; Sun, Yi; Huo, Liujie; Fu, Jun; Bian, Xiaoying; Xia, Liqiu; Tu, Qiang; Zhang, Youming
Abstract: Widely used as drugs and agrochemicals, polyketides are a family of bioactive natural products, with diverse structures and functions. Polyketides are produced by megaenzymes termed as polyketide synthases (PKSs). PKS biosynthetic pathways are divided into the cis -AT PKSs and trans -AT PKSs; a division based mainly on the absence of an acyltransferase (AT) domain in the trans- AT PKS modules. In trans -AT biosynthesis, the AT activity is contributed via one or several independent proteins, and there are few other characteristics that distinguish trans -AT PKSs from cis -AT PKSs, especially in the formation of the β-branch. The trans -AT PKSs constitute a major PKS pathway, and many are found in Burkholderia species, which are prevalent in the environment and prolific sources of polyketides. This review summarizes studies from 1973 to 2017 on the biosynthesis of natural products by trans -AT PKSs from Burkholderia species.